SAT0012 A Multi-Biomarker Disease Activity (VECTRA™ DA Algorithm) Score is Associated with Radiographic Outcomes in RA Patients Treated with TNF Inhibitors. (23rd January 2014) - Hirata, S.; Li, W.; Defranoux, N. A.; Bolce, R.; Haney, D. J.; Sasso, E. H.; Kubo, S.; Fukuyo, S.; Mizuno, Y.; Yamaoka, K.; Saito, K.; Tanaka, Y.
Abstract : Background: A novel multi-biomarker disease activity (MBDA) score that is based on the concentrations of 12 serum biomarkers has been shown to correlate with clinical disease activity in patients with rheumatoid arthritis (RA) including patients treated with TNF inhibitors (TNFi). Objectives: To explore the role of serum biomarkers to predict radiographic progression in RA patients treated with TNFi. Methods: The study was conducted at UOEH, Kitakyushu, Japan, on 141 patients who had received TNFi (IFX, ETN, ADA) for at least 1 year and had X-rays taken at baseline (BL) and week 52 of treatment. Clinical disease activity and serum biomarkers were assessed at BL and week 52 in all patients and at week 24 in 83 patients. Concentrations of VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, YKL-40, MMP-1, MMP-3, leptin, resistin, SAA and CRP were measured using a multiplex immunoassay and the MBDA score (1-100) was calculated using the validated Vectra™ DA algorithm [1 ]. Radiographic progression was determined by changes (Δ) in modified total Sharp score (mTSS) over 1 year. Correlations between ΔmTSS and disease activity measures (MBDA, DAS28-ESR, CRP) were examined using Spearman's rank correlation. Fisher's exact test was used to assess the association between radiographic progression and maintenance in high/low MBDA score among patients who had clinical and biomarker data at BL, week 24 and week 52 (n=83). Results: At baseline, patients had median (IQR) values of DAS28-ESR 5.7 (5.0-6.5), MBDA score 64 (49-76), disease duration 53 (18-167) months, and mTSS 17 (4-88.5). At 1 year, 72% of the patients had a ΔmTSS≤0.5 (non-progressors) and 9% had a ΔmTSS>3. ΔmTSS correlated with the yearly average of both DAS28-ESR (r=0.26, p=0.002) and MBDA score (r=0.33, p<0.001) across all patients (n=141). ΔmTSS also correlated with the MBDA score at week 24 and ΔMBDA score from BL to week 24 (p<0.05). In total 11 out of 12 patients with ΔmTSS>3 had a MBDA score >44 for at least 2 visits. For patients with clinical data and MBDA scores at BL, week24 and week52 (n=83), those who had MBDA scores >44 for at least 2 visits out of 3 had a greater risk of clinically relevant radiographic progression (ΔmTSS>3) compared with patients who had MBDA scores >44 in at most 1 visit (OR=15.3, p= 0.002). Patients with a MBDA score ≤29 for at least 2 visits out of 3 had a higher likelihood to be non-progressors than the others. (ΔmTSS≤0.5) (OR=14.3, p=0.002). Conclusions: For patients treated with TNFi (ADA, IFX, ETN) in a clinical practice setting low MBDA scores were associated with absence of radiographic progression while high MBDA scores were associated with markedly greater risk of radiographic progression. Response in MBDA score to treatment over the first 24 weeks correlated with radiographic outcomes at year 1. References: Curtis JR, et al., Validation of a novel multi-biomarker test to assess rheumatoid arthritis disease activity. Arthritis Care & Research 2012 Dec; 64(12):1794-803. Disclosure of Interest: S. Hirata: None Declared, W. Li Shareholder of: Crescendo Bioscience Inc., Employee of: Crescendo Bioscience Inc., N. Defranoux Shareholder of: Crescendo Bioscience Inc., Employee of: Crescendo Bioscience Inc., R. Bolce Shareholder of: Crescendo Bioscience Inc., Employee of: Crescendo Bioscience Inc., D. Haney Shareholder of: Crescendo Bioscience Inc., Employee of: Crescendo Bioscience Inc., E. Sasso Shareholder of: Crescendo Bioscience Inc., Employee of: Crescendo Bioscience Inc., S. Kubo: None Declared, S. Fukuyo: None Declared, Y. Mizuno: None Declared, K. Yamaoka Consultant for: Pfizer, Chugai Pharmaceutical Co. Ltd, K. Saito: None Declared, Y. Tanaka Grant/research support from: Bristol-Myers Squibb, MSD K.K., Chugai Pharma Co., Ltd., Mitsubishi-Tanabe Pharma Co., Ltd., Astellas Pharma Inc., Abbott Japan Co., Ltd., Eisai Co., Ltd. and Janssen Pharmaceutical K.K., Speakers bureau: Mitsubishi-Tanabe Pharma Co., Ltd., Abbott Japan Co., Ltd., Eisai Co., Ltd., Chugai Pharma Co., Ltd., Janssen Pharma K.K., Santen Pharma Co., Ltd., Pfizer Japan Inc., Astellas Pharma Inc., Daiichi-Sankyo Co., Ltd., GlaxoSmithKline K.K., Astra-Zeneca, Otsuka Pharma Co., Ltd., Actelion Pharma Japan Ltd., Eli Lilly Japan K.K., Nippon Kayaku Co., Ltd., UCB Japan Co., Ltd., Quintiles Transnational Japan Co. Ltd., Ono Pharma Co., Ltd.